2016
DOI: 10.1016/j.biombioe.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal liquefaction of spent coffee grounds in water medium for bio-oil production

Abstract: Spent coffee grounds (SCG) were liquefied in hot-compressed water to produce crude bio-oil via hydrothermal liquefaction (HTL) in a 100 cm 3 stainless-steel autoclave reactor in N 2 atmosphere. We investigated the effects of operating parameters such as retention times (5 min,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 56 publications
8
61
0
9
Order By: Relevance
“…Starting as early as the 1970s but increasing significantly over the past decade, research groups at universities and national laboratories around the world have been investigating HTL of a variety of biomass feed types, such as woody biomass (Schaleger et al, 1982;Haarlemmer et al, 2016;Tran et al, 2017), plant biomass (Zhang et al, 2013;Zhu et al, 2015;Yan et al, 2016), food processing waste (Minowa et al, 1995;Yang et al, 2016;Posmanik et al, 2017), agricultural waste (Chan et al, 2014;Singh et al, 2015;Zhu et al, 2017), animal manure (Xiu et al, 2010;Theegala and Midgett, 2012), pulp/paper sludge (Xu and Lancaster, 2008), and algae Neveux et al, 2014;Faeth et al, 2016). Previous work in CHG over the same period has looked at conversion of agricultural waste (Pei et al, 2009) and industrial wastewater (Seif et al, 2016) to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Starting as early as the 1970s but increasing significantly over the past decade, research groups at universities and national laboratories around the world have been investigating HTL of a variety of biomass feed types, such as woody biomass (Schaleger et al, 1982;Haarlemmer et al, 2016;Tran et al, 2017), plant biomass (Zhang et al, 2013;Zhu et al, 2015;Yan et al, 2016), food processing waste (Minowa et al, 1995;Yang et al, 2016;Posmanik et al, 2017), agricultural waste (Chan et al, 2014;Singh et al, 2015;Zhu et al, 2017), animal manure (Xiu et al, 2010;Theegala and Midgett, 2012), pulp/paper sludge (Xu and Lancaster, 2008), and algae Neveux et al, 2014;Faeth et al, 2016). Previous work in CHG over the same period has looked at conversion of agricultural waste (Pei et al, 2009) and industrial wastewater (Seif et al, 2016) to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Key aspects of process development in terms of catalyst performance and stability should also be investigated . Ultimately, direct liquefaction to improve the quality of bio‐oil requires less upgrading and would reduce diluent costs …”
Section: Resultsmentioning
confidence: 99%
“…86 Ultimately, direct liquefaction to improve the quality of bio-oil requires less upgrading and would reduce diluent costs. [115][116][117] In this study, the model assumes solid contents of ~8.2% in the slurry; this would need a larger reactor volume to handle water during the HTL process. Hence, further research needs to consider scale-up and the feasibility of pumping slurry with high solids content.…”
Section: Challenges and Key Insightsmentioning
confidence: 99%
“…The continuous HTL was done at a feed rate of 120 L/h, which translates into a residence time of 10 min for the HTL run. The yield obtained when using a residence time of 10 min was 28.5% and 15.2% for the bio-crude and the bio-char respectively Yang et al [11] did batch HTL on SCG in water to test the effect on the yield of the bio-oil at different reaction parameters. The study concluded that a shorter retention time gave the best bio-oil yield, which was 31.63%.…”
Section: ) Continuous Htl Oil Yieldmentioning
confidence: 99%